Nutritive value of fermented coconut meal and its inclusion in ration of male ducklings - A.P. Sinurat; P. Setiadi; T. Purwadaria; A.R. Setioko; Jinadasa Dharma (Indonesian Center for Animal Research and Development (ICARD), 1995)
An experiment was conducted to study the metabolizable nutrients of fermented and non-fermented coconut meal for ducks. The study was also followed by a feeding trial on male ducklings. Assay on the metabolizability of nutrients (energy, protein, dry matter, and phosphorus) of the feedstuffs were conducted by total collection method. Results of the study showed that the metabolizable-energy, protein, dry matter and phosphorus of non-fermented coconut meal were 1,667 Kcal/kg, 31 .3%, 60% and 23%, as compared to 2,473 Kcal/kg, 36.3%, 63.2% and 36.1% for the fermented coconut meal, respectively. The feeding trial was designed to study the tolerance of ducklings to fermented or non-fermented coconut meal at 0, 10, 20 and 30% in the diet . Results showed that non-fermented coconut meal can be included in the diet of ducklings up to 30% with no growth depression . The use of fermented coconut meal at 10%, 20% or 30% depress growth of ducklings at early stage of growth (until 5 weeks of age), with no effect on feed consumption. The growth depression, however was not observed at older age. Based on the final body weight and feed conversion ratio it is recommended that the fermented coconut meal should not be included more than 20% in the diet of male ducklings .